'Florida White Ruffles' Caladium - A University of Florida Cultivar - Baldwin D. Miranda; G. J. Wilfret; Brent K. Harbaugh (EDIS)
Caladium [Caladium bicolor (Ait.) Vent., syn. Caladium x hortulanum Birdsey, Araceae Juss.] are popular foliage plants possessing great diversity in the shapes, sizes, and colors of their leaves. They commonly are sold as potted plants in the florist trade, as tubers for use in landscapes or home gardens, or as bedding plants for late spring or early summer (Harbaugh and Tjia, 1985). Although more than 1500 named cultivars have been introduced during the past 100 years (Hayward, 195), only 90 were found to be in commercial production in 1998 (Bell and Wilfert, 1998).